The Differences in English Proficiency of Students with Different Learning Style - Suci Sahriyah; Junaidi Mistar; Nuse Aliyah Rahmati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This research investigated the significant differences in English proficiency of students with different learning styles among the 5th-semester students at the University of Islam Malang. The research was in the form of Ex-Post facto design. The researcher took the sample which consists of 48 students. This research used cluster sampling classified as the process of taking the sample. The data were gained by using a learning style questionnaire and TOEFL test. The data were analyzed by one-way ANOVA on IBM SPSS Statistic 25. The researcher also provides a nonparametric test, the Kruskal-Wallis test. The results showed that 1) The calculation from the One-Way ANOVA listening test described that there was no significant difference in listening mastery among students whose learning styles are visual, auditory and kinesthetic (F= 0.868, p<0.427); 2) The calculation from One-Way ANOVA structure test described that there was no significant difference in structure mastery among students whose learning styles are visual, auditory and kinesthetic (F= 0.245, p < 0.777); and 3) The calculation from Kruskal-Wallis test the significant value of reading comprehension test is p < 0.416. It is clearly stated that the result is not significant. It was concluded that there were no significant differences in students’ English proficiency among students whose learning styles are visual, auditory, and kinesthetic. The researcher hoped that the future researcher can use another learning style that is more specific and more detailed.